TERRITORIAL FEATURES OF AGE-SEX STRUCTURE OF THE POPULATION OF THE SUMY REGION - Корнус, Олеся (Human Geography Journal, 2014)
The article analyzes the dynamics of the age and sex structure of the population of the Sumy region for the years 2001-2012. The spatial and temporal dimensions of the interrelation between men and women are considered. The average age of the population, the demographic burden on the working population, the life expectancy are also considered. Age-sex pyramid and cartographically shows the distribution of the resident population by age groups by administrative district of the Sumy region are building. Calculate the rate of population health Sumy region and analyzed its dynamics.